Construction and demolition waste management in developing countries: a diagnosis from 265 construction sites in the Lima Metropolitan Area - Rondinel Oviedo, Daniel Ricardo (2021)
The construction industry is a driver of economic and social development in developing countries; however, it is also one of the primary sources of entropic elements such as construction and demolition waste (CDW). Since construction is expected to continue growing, it is essential to study the CDW status under these scenarios. To the best of the author’s knowledge, this is the first academic research in Peru that deals with CDW. The information for the research is collected from primary and secondary sources, which includes 265 surveys, interviews, and visits to construction and disposal sites. The results are obtained from a cross-analysis of the influence of different aspects (experience and education level of the construction site manager, dimension, or socio-economical level of the site, building use, among others) on CDW management. Further, significant findings related to each stage of the CDW cycle are presented. The obtained findings provide information for effective decision making in terms of policies and regulations on CDW, which will help improve its management, reduce environmental impact, and provide economic benefits, especially in developing countries.